Caribbean equity markets and intra-CARICOM capital movements - Bissember, Enid E. ([s.n.] [S.l.]GY, 1997)
Examines the equity markets in the Caribbean and their impact on intra CARICOM capital movement. Discusses the likely benefits of an integrated equity market for the region. Argues that the liberalization of the foreign exchange markets in the region along with the introduction of new telecommunications facilities has helped to break down former barriers to cross border trade in equity.